Analisis Rantai Nilai dan Struktur Pasar Komoditi Getah Pinus di Hutan Kemasyarakatan Cempalagie Indonesia: Value Chain Analysis and Market Structure of Pine Sap Commodity in Community Forest Area Case in Indonesia - Andi Mawaddah Zakiyah; Makkarennu; Ridwan (Forestry Faculty of Hasanuddin University, 2025)
Community Forestry (HKm) is a scheme that aims to empower local communities and provide access to manage protected/production forest areas. The pine resin commodity is one of the sources of livelihood for the community in the Cempalagie HKm area by utilizing existing access. Value chain analysis is very important to find out the pine resin commodity business actors in the marketing chain from upstream to downstream, namely from raw materials to become a product through qualitative methods with a descriptive approach. The results of the value chain analysis will then show the market structure in the form of market type, number of sellers and buyers, product differentiation, entry barriers, cost structure and conglomeration formed in each chain. The number of respondents was selected as 30 households by census based on respondents who work as pine resin tappers. The results showed that pine resin commodity business actors consisted of tappers, intermediary traders and wholesalers or pine resin processing industries in which the flow of goods, information and money occurred and marketed pine resin and pine resin products in the form of gondorukem, turpentine, alpha pinene and delta carene to international markets, namely India, Vietnam and China.